PERLINDUNGAN HUKUM BAGI KORBAN PENIPUAN BERKEDOK CINTA PADA APLIKASI TINDER MENURUT HUKUM POSITIF INDONESIA: Studi Kasus Terhadap Putusan Pengadilan Negeri Surabaya Nomor 2414/Pid.B/2020/PN.SBY - Bernadeta Dwi Novernia, (2023)
Technological developments that are used by everyone for various reasons have given rise to the online dating phenomenon. This is an opportunity for irresponsible people to commit crimes, one of which is fraud under the guise of love. Through this paper, it is hoped that the public will understand the practice of criminal acts and the optimization of law according to Indonesian positive lawThe purpose of this research is to know the practice of fraud under the name of love and to find out the optimization of legal protection for victim against criminal act of fraud under the name of love. The research method used is a normative juridical approach through a statutory approach and case approach. Types sources of legal materials that used in this research are primary legal sources that consist criminal code law, ITE Law, and verdict from Surabaya District Court Decision No. 2414/Pid.B/2020/ PN. SBY. The result are that the practice of criminal acts of fraud under the name of love begins with identity forgery and ends up with the victim cost do much material. It is regulated in Article 378 of the Criminal Code Law and Article 28 Paragraph 1 of the ITE Law which is included the direct crime of fraud that uses the Tinder Application as a platform for perpetrators to carry out their method. Form Perpetrator's punishment are imprisonment for 4 years and maximum fine of one billion rupiah. Optimizing legal protection for victims is the provision of rights and obligations and improving the security system of Tinder Application. Prevention from society need to be done so as not to become a victim.